THE EFFECT OF SALINITY ON OXYGEN TRANSFER PROCESS IN LEACHATE WITH A LOW INITIAL COD CONCENTRATION - Moh Rizal Ngambah Sagara; Mega Mutiara Sari; Iva Yenis Septiariva; I Wayan Koko Suryawan (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2022)
Leachate is one of the results of rainwater infiltration and the degradation of microorganisms in waste. Some leachate types usually contain salinity which is an inhibitor in biological treatment processes. Aerobic biological treatment usually also requires sufficient dissolved oxygen (DO) levels. This study aimed to determine the effect of salinity on oxygen transfer in saline leachate. This study used a DO meter to measure the DO concentration in the 2 L volume reactor. There were two variations, namely leachate without salinity and with salinity 6 ppt, where the processing was carried out with three repetitions. The final oxygen transfer coefficients for the leachate without salinity and with salinity were 0.021 and 0.014, respectively. While the detention time required for leachate without salinity is 47.5 minutes, it takes 71.43 minutes with salinity.